“My Servant Job Shall Pray for You” - Balentine, Samuel E. 1950- (2002)
This article reads between the lines of the book of Job—with the aid of artists' renderings of Job as a pray-er—to explore what God may be endorsing when God says, “My servant Job shall pray for you” (42:8). The conventional view, which understands Job to pray for the forgiveness of his foolish friends, is deeply rooted in Jewish and Christian piety, and with good reason. Several clues suggest that a nonconventional view, which understands Job to have been praying that God not act in foolish ways, also deserves careful attention. In this view, Job models a way of contending for justice that God applauds and expects from those who would be “servants” of God.